(3CSGSjGJ GdajRjGA (B/ s - (3HhT,a,s; (3GdLRjQj,SYjO,s; (3SdjeGf,eMeO Cejf,s; (3GdfGOi,eMeO YHO GdebUhO,s ((3GdbGgQI(B[(3eUQ(B] : s (3eDSSI GdGgQGe, s, 1982)
(3dbO hLO chffG efP eGjbGQH (B11(3edjhf SfI Ydi gjFI cQI SGNfI PGJ cKGaI gGFdI Ke JeOOJ Jdc GdcQI HSQYI hHQOJ hgj dGRGdJ JJeOO hYfOeG JeOOJ hHQOJ GOJ Gdi JZjQGJ aj GdcJdI Gdi XghQ efGWb ef GdeGOI GdeJcKaI aJchfJ GdeLQGJ(B.s
(3jJVef edGMb(B.s
(3jJVef bGFeI HGdeUWdMGJ GdYdejI GfLdjRj YQHj,UaMI(B887-924.s
(3jJVef agQS(B.s
Keywords: (3GdajRjGAs